Grafe Fruit Extract (Vitis vinifera) as an antioxidant - Hartono; I Nyoman Ehrich Lister; Buter Samin (International Journal of Health and Pharmaceutical (IJHP), 2022)
One plant that is believed to have anti-diabetic effects is grapes (Vitis vinifera), which contains polyphenol compounds. The antioxidant and anti-postprandial hyperglycemics of grape extract show potential in treating diabetes. This study is an experimental study that aims to explore grape extract extracts as antioxidants through testing (DPPH, ABTS, LC-MS/MS). Based on the test results, grape extract contains very high phytochemicals, including terpenoids and alkaloids, and antioxidant test results found DPPH with an average IC50 value of 21.49 g / mL and at the lowest concentration (6.25 g / mL). The GFE also showed the highest antioxidant activity against ABTS trapping with an average IC50 value of 74.07 g/mL and LC-MS/MS results obtained grape extract samples containing 0.00001% chlorogenic acid and querce-tin compounds of 0.00012%.